A note on challenges and opportunities for Operations Research in hospital logistics - Teresa Melo (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2012)
Ancillary services such as those provided by logistics seem simple and straightforward, yet their role is often overlooked by hospitals. Recent studies indicate that logistics-related activities impact significantly on the quality of health care as well as on hospital costs. Hospital logistics contributes to the provision of care to patients by ensuring that all required services and resources (i.e. staff, facilities, and equipment) are delivered at the right time. In the current context of cost containment, where hospitals must carefully manage public funds, improving the management of these scarce resources has become more and more pressing. Operations Research provides methodologies to support the logistical operations of hospitals and assist in process optimization. In this article we examine the challenges and opportunities faced by operations researchers working in the hospital sector. We also discuss ways of raising the awareness of hospital managers and health care professionals for the benefits of using Operations Research models and solution techniques to improve resource management.
Keywords: 650; Hospital logistics; Operations Research; Application areas; Krankenhaus; Prozessmanagement; Prozessmanagement; Logistik; Operations Research